Digital Transformation: The Effect of Learning Management Systems in Developing Employee Digital Competence: Study at A Chemical Company in Gresik - Muhammad Zidan Nasih; Sugeng Ali Mansur (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
The swift advancement of information technology in the Industrial Revolution 4.0 age, progressing towards Society 5.0, has underscored the vital significance of digital transformation for industries. Digital transformation is a crucial strategy for enterprises to ensure business continuity, improve operational efficiency, and sustain competitiveness in a constantly changing industrial landscape. This study examines the function of Learning Management Systems (LMS) in enhancing employees' digital competencies and its resultant effect on attaining digital transformation in a chemical firm located in Gresik, Indonesia. The study used a quantitative methodology with an explanatory research design, examining the interrelations among LMS, digital competence, and digital transformation through route analysis. Data were gathered from 95 employees across multiple areas of the organization using standardized questionnaires. The research utilized primary data from participants and secondary data from literature reviews of books, journals, and pertinent papers. The questionnaires aimed to assess perceptions of LMS usage, the growth of digital competence, and advancements in digital transformation. Data research indicated that LMS has a favorable and considerable impact on enhancing employees' digital competencies. Moreover, improved digital proficiency immediately and substantially facilitates the effective execution of digital transformation within the firm. The results indicate that LMS is essential for employee training, offering a flexible and accessible learning environment that promotes self-directed learning and adaptability to emerging technology. By providing employees with essential digital competencies, LMS improves individual performance and aids organizational achievement in addressing the challenges of the digital age. The study highlights the indirect influence of LMS on digital transformation via enhanced digital competence, stressing the interrelation of these factors in fulfilling organizational goals. The report provides actionable insights for organizations aiming to expedite digital transformation by utilizing LMS as a strategic asset for employee development. It underscores the need to invest in superior LMS platforms and connect them with company objectives and policies to guarantee active employee engagement. Furthermore, the research paves the way for further investigation into factors affecting the relationship among LMS, digital competence, and digital transformation, including organizational culture, leadership, and the degree of technology use. This study underscores the essential function of LMS in enhancing digital competence and facilitating digital transformation within industries, specifically in the context of the chemical industry in Gresik. It offers critical insights for firms seeking to fortify their digital strategy, augment personnel competencies, and elevate competitiveness in the global marketplace. These findings further enhance the broader academic conversation regarding the interaction between digital learning platforms, workforce competency, and organizational change in the digital era.